Under the Long Shadow of Europe - Greeks and Turks in the era of Postnationalism - Nicolaidis, K (Brill, 2009)
Under the Long Shadow of Europe - Greeks and Turks in the era of Postnationalism, edited with Kerem Öktem and Othon Anastasakis, The Hague: Brill, 2009